MAXIMIZING THE COMPETENCE IN THE NOVEL OUT OF MY MIND (2010) BY SHARON M. DRAPER - Indri Mariska Safitri; Kurnia Ningsih (English Language and Literature, 2019)
The purpose of the analysis is to expose the issue of maximizing the competence done by the main character with cerebral palsy to use all of her efforts in order to reach the equality with normal people. This analysis is using text based and context based method. The text based is using character, plot and setting. The context based  is related to the concept of life instincts by Freud, the concept of self-awareness by Crisp-Turner. The result of this analysis shows the protagonist succeeds to maximize her competence through participating in competition and social life.